Structural impairment patterns in peripapillary retinal fiber layer and retinal ganglion cell layer in mitochondrial optic neuropathies - Teng, Da; Peng, Chun-Xia; Qian, Hai-Yan; Li, Li; Wang, Wei; Wang, Jun-Qing; Chen, Bing; Zhou, Huan-Fen; Wei, Shi-Hui (International journal of ophthalmology, 2018)
To evaluate the structural injure patterns in peripapillary retinal fiber layer (pRNFL), retinal ganglion cell layer (RGCL) and their correlations to visual function in various mitochondrial optic neuropathies (MON) to offer help to their differential diagnosis. Totally 32 MON patients (60 eyes) were recruited within 6mo after clinical onsets, including 20 Leber hereditary optic neuropathy (LHON) patients (37 eyes), 12 ethambutol-induced optic neuropathy (EON) patients (23 eyes), and 41 age-gender matched healthy controls (HC, 82 eyes). All subjects had pRNFL and RGCL examinations with optic coherence tomography (OCT) and visual function tests. In the early stages of MON, the temporal pRNFL thickness decreased (66.09±22.57 µm), but increased in other quadrants, compared to HC (76.95±14.81 µm). The other quadrants remaining stable for LHON and EON patients besides the second hour sector of pRNFL thickness reduced and the temporal pRNFL decreased (56.78±15.87 µm) for EON. Total macular thickness in MON reduced remarkably (279.25±18.90 µm; =0.015), which mainly occurring in the inner circle (3 mm diameter of circle) and the nasal temporal sectors in the outer circle (5.5 mm diameter of circle), in contrast to those in HC. RGCL thickness reduced in each sector of the macula (61.90±8.73 µm; ≤0.001). It strongly showed the correlationship of best corrected visual acuity ( =0.50, =0.0003) and visual field injury ( =0.54, =0.0002) in MON patients. OCT is a potential tool for detecting structural alterations in the optic nerves of various MON. Different types of MON may have different damage patterns.